Adjuvant therapy in patients with stage II and III colon cancer under 70 years of age. (June 2013) - Dumont, Sarah N; Chibaudel, Benoist; Bengrine-Lefèvre, Leïla; André, Thierry; de Gramont, Aimery
SUMMARY  Colorectal cancer is a common malignancy and its prognosis has improved over recent decades due to sustained efforts of the scientific community. This review focuses on adjuvant therapy across the lifespan of patients under 70 years of age. Here, we discuss the standard management of patients with stage III colon cancer, consisting of fluoropyrimidines and oxaliplatin combination for 6 months. The specific issues faced by patients with stage II colon cancer, including adjuvant chemotherapy in high-risk patients, are discussed. Finally, we describe the distinctive characteristics of patients with colon cancer under 40 years of age and the prospects of adjuvant chemotherapy in patients with colon cancer.